Gap analysis between BNM regulation and musharakah mutanaqisah application in Islamic banking - Rahman, Audia Syafa'atur; Ahamed Hilmy, Hayathu Mohammed; Saifurrahman, Adi; Hassan, Rusni (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM)., 2018)
Bank Negara Malaysia resolved the utilization of Musharakah Mutanaqisah on the Shari’ah Advisory Committee 56th meeting in 2010. In practice, most of the banks have adopted Musharakah Mutanaqisah for the purpose of home financing. This study examines the gap between the BNM regulation and as practiced by Maybank Islamic and HSBC Amanah. The method of analysis adopts a qualitative study based on the library research. The study discovered one major gap and three minor gaps. The major gap is related to charging an early settlement fee by HSBC Amanah. In addition, three minor gaps are related to wa’ad statement in both banks, the pledge statement with respect to Maybank, and default approach compliance in both banks. However, this study does not examine the gap that related to the contract validity. Nevertheless, the discovery of a single gap found may affect contract validity of the product. This study recommends for better monitoring and supervision conducted by all stakeholders. BNM Shari’ah Advisory Council and respective Islamic bank committees should verify the practice that may cause the contract to become void. In addition, Islamic financial institutions should strictly follow all the regulations issued by the Bank Negara Malaysia in all their practices and publication in order to make the contracts acceptable according to Shari’ah and to cater public confidence. Adhering to guidelines along with the Shari’ah standard of the product further increases accountability and trustworthy of Shari’ah compliance in a particular product.